Sínteses e estudos biológicos de novos complexos de prata(I) de hidrazonas e de ácidos N,R-sulfonilaminobenzóicos - Cleidivânia Silveira Rocha (2019)
Thirteen new silver(I) complexes with hydrazones derived from 5-nitro-2-furaldehyde and N,R-sulfonylaminobenzoic acids were synthesized in order to obtain a series of antimicrobial, cytotoxic and trypanocidal metallopharmaceutical candidates. [Ag(MeH)2]NO3 (1), [Ag(PhH)2NO3] (2), [Ag(pNO2)2]NO3 (3) [Ag(pHCl)2]NO3 (4) and [Ag(oHCl)2NO3] (5) were obtained with the hydrazones N'-((5-nitrofuran-2-yl) methylene)acetohydrazide [MeH], N'-((5-nitrofuran-2-yl)methylene)-benzohydrazide [PhH], 4-nitro-N'-((5-nitrofuran-2-yl)methylene)-benzohydrazide [pNO2], 4-chloro-N'-((5-nitrofuran-2-yl)methylene)-benzohydrazide [pHCl] and 2-chloro-N'-((5-nitrofuran-2-yl)methylene)-benzohydrazide [oHCl]. [AgMH1] (6), [AgMH2] (7), [AgMH3] (8), [AgMH4] (9), [AgMH5] (10), [AgMH6] (11), [AgMH7] (12) and [AgMH8] (13) complexes were obtained with 4-((3-nitrophenyl)sulfonamide)benzoic acid [MH1], 4-((4-nitrophenyl)sulfonamide)benzoic acid [MH2], 3-((2-nitrophenyl)sulfonamide)benzoic acid [MH3], 3-((3-nitrophenyl)sulfonamide) benzoic acid [MH4], 2-((2-nitrophenyl)sulfonamide)benzoic acid [MH5], 2-((3-nitrophenyl)sulfonamide)benzoic acid [MH6], 2-((4-nitrophenyl)sulfonamide)benzoic acid [MH7] and 3-((4-chlorophenyl)sulfonamide)benzoic acid [MH8]. Hydrazones MeH, pNO2 and pHCl crystallized in conformation E in relation to the C3-N2 bond and their complexes (1), (2) and (5) presented distorted octahedral arrangement, slightly distorted quadratic pyramidal geometry and distorted octahedral geometry, respectively. X-ray powder diffraction revealed that the structural arrangement in the powder is the same as that of the crystal. The complexes containing N,R-sulfonylaminobenzoic acids (6-12) the carboxylate group is coordinated to silver(I) in an anisobident mode and complex (13) in a bidentate mode, suggesting a polymeric system for all complexes. Crystallographic analysis showed that the geometry of complex (12) is distorted tetrahedral, resulting in an OOOCAg ··· AgOOOC environment in the polymeric complex. X-ray powder diffraction analysis for MH7 and (12) indicated that the ligands and complex systems in the powder are different from those observed in the single crystal. Hydrazones and their silver(I) complexes showed significant antifungal action, being more active against Candida tropicalis, Candida lusitaniae and Candida parapsilosis species than silver nitrate, silver sulfadiazine, miconazole nitrate and nystatin, which are the reference drugs. These compounds showed cytotoxic activity against tumor cells B16F10 (mouse metastatic melanoma) and 4T1 (mouse metastatic mammary adenocarcinoma cells), however, they were also toxic to healthy BHK-21 (normal kidney cells) cells. Hydrazones and their silver(I) complexes were active against intracellular forms of Trypanosoma cruzi and were more potent than the reference drug benznidazole. Among the tested compounds, MeH, oHCl, (1) and (2) were the most promising ones due to the high values obtained for the selectivity indices (IS, IS> 88). These compounds did not show satisfactory antibacterial activity. Fluorescence spectroscopy and Isothermal Titration Calorimetry (ITC) studies have shown that human serum albumin (HSA) interacts with silver(I) complexes derived from hydrazones (complexes 1-5) and N,R-sulfonylaminobenzoic acids ( complexes 8, 10-13). The fluorescence suppression mechanism was static with moderate binding force, suggesting that the compounds could be transported by HSA in the bloodstream to their target. Thermodynamic binding parameters indicated thermodynamic stability and spontaneity of binding. In addition, according to fluorescence spectroscopy, interactions between HSA and complexes (1) and (2) had a higher predominance of hydrogen bonds and van der Waals forces. ITC data showed that MeH and PhH weakly bind albumin. However, interactions of complexes (1) and (2) with HSA showed that there are at least three binding sites occurring for each compound with HSA, with moderate strength. The complex (1)/HSA system had a predominance of electrostatic and hydrophobic interactions. Similarly, for the complex (2)/HSA system, with predominance of hydrophobic and van der Waals forces and with hydrogen bonding between the phenyl ring hydrogens and the amino acid residues of the HSA. The biological results obtained in the present work showed that silver(I) hydrazone compounds are promising and should be investigated in vivo studies.